Membangun Ekonomi Mandiri Di Desa Segara Katon Melalui Pendampingan Usaha ProduksiTiu Pupus Virgin Coconut Oil(VCO) - Masdiyanto Masdiyanto; Deding Wadi; Abdul Gapur; Maulana Eka Derita; Emi Lastuti; Raden Abdul Rasyid; Komang Aditya Arya Nugraha; Pathurrahman Pathurrahman; Ni Nengah Supriatini; Muliadi Muliadi; Najamuddin Najamuddin; Rukakyah Rukakyah; Sandi Justitia Putra; Lalu Ahmad Rahmat; I Made Putra Suryantara (Puslitbang Sekawan Institute Nusa Tenggara, 2022)
Real Work Lecture (KKN) Group VIII University of 45 Mataram was held in Segara Katon Village. One of the flagship programs that became the output of the KKN activity was the Virgin Coconut Oil (VCO) product produced by the Putri Kembang Kerurak Women Farmers Group (KWT). The KWT is fostered to carry out production to product marketing. The method used is in the form of training which is carried out for 4 days so that the KWT is ensured to understand the overall technical production. The success of this activity was able to become a locomotive for building an independent economy in Segara Katon Village. KWTs in other hamlets were enthusiastic to immediately imitate and cooperate. There are quite a number of consumers of VCO products, the number of coconut plants in Segara Katon Village which is very supportive, and the selling price of profitable products can improve the welfare of the community.